The Influence of Service Quality and Facilities on Consumer Satisfaction - Riska Anggraini; Dwi Widi Hariyanto; Endang Muryani (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2024)
The food business is one of the businesses that is growing rapidly and has the potential to grow quite large. Many business people have already benefited from this culinary business. In the culinary business, you must be able to create many innovations in order to meet the needs and desires of consumers.The main thing that must be prioritized in conditions of intense competition is the satisfaction of service users in order to survive, compete and dominate the market. The purpose of this study is to determine the effect of quality of service and facilities simultaneously and partially on customer satisfaction Ayam Bakar Pak “D” Branch Ketintang I Surabaya. The sample of this research is the visitors of Ayam Bakar Pak “D” Branch Ketintang I Surabaya, with a total sample of 100 respondents. The analysis technique uses Multiple Linear Regression with SPSS programs or software. The results showed that jointly (simultaneously) showed that the quality of service and facilities affect customer satisfaction, partially the quality of service has a positive and significant effect on customer satisfaction, as well as partially the facility has a positive and significant effect on customer satisfaction .